Complex Chromosomal Rearrangement Causes Male Azoospermia: A Case Report and Literature Review - Liang, Yi; Xie, Yingjun; Kong, Shu; Pan, Qianying; Qiu, Wenjun; Wang, Ding; Li, Mengting; Lin, Sisi; Liu, Zihang; Sun, Xiaofang (Frontiers in Genetics, 2022)
Background: Male carriers of complex chromosomal rearrangements (CCRs) may have decreased fertility and usually present with azoospermia, oligospermia or teratospermia. Methods: High-resolution karyotype analysis using G-banding on peripheral blood lymphocytes was performed in an azoospermic male. Copy number variations (CNVs) were detected by chromosomal microarray analysis, and genetic variations were determined by long-read nanopore sequencing with Sanger sequencing for breakpoint confirmation. Results: The karyotype of the patient was 46,XY,t(4;21)(p11;p11),t(5;6;14) (p13q22;p22q22;q22), which did not involve CNVs with clinical significance. Twelve breakpoints in chromosomes 5, 6 and 14 were found by long-read nanopore sequencing. Reports on 17 males carrying CCRs with azoospermia were also reviewed. Conclusion: The extent of asynaptic regions in synaptonemal complexes during pachytene and the disruption of genes involved in male gametogenesis may cause azoospermia in CCR carriers.